2021
DOI: 10.1557/s43578-021-00403-2
|View full text |Cite
|
Sign up to set email alerts
|

Shaping and properties of thermoplastic scaffolds in tissue regeneration: The effect of thermal history on polymer crystallization, surface characteristics and cell fate

Abstract: Thermoplastic semi-crystalline polymers are excellent candidates for tissue engineering scaffolds thanks to facile processing and tunable properties, employed in melt-based additive manufacturing. Control of crystallization and ultimate crystallinity during processing affect properties like surface stiffness and roughness. These in turn influence cell attachment, proliferation and differentiation. Surface stiffness and roughness are intertwined via crystallinity, but never studied independently. The targeted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 77 publications
(104 reference statements)
0
9
0
1
Order By: Relevance
“…Gelatin's primary functional groups are composed of carboxylic, amide, ester, aromatic and alkane 35 . Data from previous study suggested that a high crystallinity biomaterial demonstrated a high degree of stiffness, which may in turn inhibit cell attachment 36 . Nonetheless, our results demonstrated a lower intensity of amide peak upon genipin induced gelatin crosslinking via the free amide group, but the amorphous structure remained, which may facilitate the growth of MSCs.…”
Section: Discussionmentioning
confidence: 97%
“…Gelatin's primary functional groups are composed of carboxylic, amide, ester, aromatic and alkane 35 . Data from previous study suggested that a high crystallinity biomaterial demonstrated a high degree of stiffness, which may in turn inhibit cell attachment 36 . Nonetheless, our results demonstrated a lower intensity of amide peak upon genipin induced gelatin crosslinking via the free amide group, but the amorphous structure remained, which may facilitate the growth of MSCs.…”
Section: Discussionmentioning
confidence: 97%
“…Paralelamente, os polímeros sintéticos representam uma escolha de aplicabilidade de scaffolds nos tecidos duros possuindo características físicas como rigidez do material, rugosidade e topografia desejáveis para a neoformação celular (CALORE et al, 2021).…”
Section: Discussionunclassified
“…Thermoplastic semi-crystalline polymers are excellent candidates for developing tissue-engineered scaffolds as they are easy to process and present adjustable properties. In parallel, synthetic polymers can be an option for scaffolds applicability in hard tissues, presenting physical characteristics such as material stiffness, roughness, and topography that are desirable for cell neoformation (Calore et al, 2021). Calore et al (2021) indicated that in an osteogenic environment, human mesenchymal stromal cells responded more to surface roughness than to surface stiffness of different scaffolds.…”
Section: Discussionmentioning
confidence: 99%